Effect of the substitutional elements on the microstructure of the Ti-15Mo-Zr and Ti-15Zr-Mo systems alloys - Correa, Diego Rafael Nespeque [UNESP]; Vicente, Fábio Bossoi [UNESP]; Araújo, Raul Oliveira [UNESP]; Lourenço, Mariana Luna [UNESP]; Kuroda, Pedro Akira Bazaglia [UNESP]; Buzalaf, Marília Afonso Rabelo; Grandini, Carlos Roberto [UNESP] (Elsevier, 2015)
Titanium alloys have excellent biocompatibility, and combined with their low elastic modulus, become more efficient when applied in orthopedic prostheses. Samples of Ti-15Mo-Zr and Ti-15Zr-Mo system alloys were prepared using an arc-melting furnace with argon atmosphere. The chemical quantitative analysis was performed using an optical emission spectrometer with inductively coupled plasma and thermal conductivity difference. The X-ray diffractograms, allied with optical microscopy, revealed the structure and microstructure of the samples. The mechanical analysis was evaluated by Vickers microhardness measurements. The structure and microstructure of alloys were sensitive to molybdenum and zirconium concentration, presenting α′, α″ and β phases. Molybdenum proved to have greater β-stabilizer action than zirconium. Microhardness was changed with addition of molybdenum and zirconium, having Ti-15Zr-10Mo (436 ± 2 HV) and Ti-15Mo-10Zr (378 ± 4 HV) the highest values in each system.
Keywords: Ti Alloys; Biomaterials; Microstructure